(untitled) - Breithaupt, Jim (London, 1999)
The book offers various routes into the subject via independent introductory sections in waves, materials, mechanics and electricity. It develops sections on fields, electromagnetism, electrons, atomic and nuclear physics and advanced mechanics and thermodynamics.
Keywords: Physics